Flame Stability And Fuel Efficiency Of Gas Diffusion Flame On The Backward Facing Step - Harinaldi Harinaldi; Maymuchar Maymuchar (Testing Center for Oil and Gas LEMIGAS, 2009)
Propane and butane injection into the recirculation zone in the fuel area with backward-facing step has a significant effect to the diffusion flame with the characteristic stability which depends on the velocity of the free air stream, the injection position from the step and the injection position to step height ratio. The test result shows that there are two main stable diffusion flames: a stabilized flame in the recirculation zone and a stabilized flame in the shear layer region. There is a decrease of the fuel efficiency due to the effect of the greater ratio of the injection position to the step height and the farther injection position from the steps. The effect of the free air stream velocity is much more significant the injection location near the steps.